ANALISIS PENGGUNAAN METODE ALTMAN (Z-SCORE) DALAM MEMPREDIKSI TERJADINYA FINANCIAL DISTRESS PADA PERUSAHAAN MINYAK BUMI DAN GAS (MIGAS) YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2010-2014 - Ilmi Furqan Al Annuri; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study is to determine and analyze the predictions of financial distress in oil and gas companies registered in the Indonesia Stock Exchange (IDX) 2010-2014 period using the Altman (Z-Score) method. By using the type of quantitative research and descriptive analysis method, it is found that PT. Energi Mega Persada, Tbk indicated financial distress in the year 2010-2012. While in 2013, PT. Benakat Integra, Tbk is classified as a company experiencing financial distress. Furthermore, in 2014 PT. Benakat Integra, Tbk and PT. Energi Mega Persada, Tbk indicated as financial distress companies.Keywords : Financial distress, Altman (Z-Score) method.